Lattice Monte Carlo analysis of thermal diffusion in multi-phase materials - Fiedler, Thomas (Springer, 2011)
This Chapter addresses the numerical simulation of thermal diffusion in multi-phase materials. A Lattice Monte Carlo method is used in the analysis of two- and three-dimensional calculation models. The composites considered are assembled by two or three phases, each exhibiting different thermal conductivities. First, a random distribution of phases is considered and the dependence of the effective thermal conductivity on the phase composition is investigated. The second part of this analysis uses a random-growth algorithm that simulates the influence of surface energy on the formation of composite materials. The effective thermal conductivity of these structures is investigated and compared to random structures. The final part of the Chapter addresses percolation analyses. It is shown that the simulation of surface energy distinctly affects the percolation behavior and therefore the thermal properties of composite materials.